Memahami Makna dan Pentingnya Supervisi Pendidikan Pada Peningkatan Kinerja Guru - Akram Maulana Yamin; Davin Malik Alfaruqi; Ermita; Fifin Wildanah (CV. ITTC INDONESIA, 2025)
Educational supervision is a crucial aspect in improving the quality of teaching and learning in schools. Optimal teacher performance relies heavily on their ability to implement effective and innovative teaching methods, which can be achieved through educational supervision. This article aims to discuss the meaning, importance, and role of educational supervision in enhancing teacher performance. Through a literature review, this article analyzes various concepts of educational supervision as presented by several experts, including the objectives, functions, and types of supervision that can be applied in schools. Academic supervision and clinical supervision are two commonly used types of supervision, each having different goals and approaches in supporting teachers' professional development. The findings indicate that educational supervision serves not only as a monitoring tool but also as a strategy for empowerment that helps teachers identify problems, improve competencies, and enhance overall teaching quality. With the right approach, supervision can create a more conducive learning environment, increase teacher motivation, and ultimately contribute to achieving better educational outcomes.